A Study of Hormonal Receptors in Esophageal Carcinoma: Northeast Indian Tertiary Cancer Center Study - Kalita, Deepjyoti; Bannoth, Srinivas; Purkayastha, Joydeep; Talukdar, Abhijit; Das, Gaurav; Singh, Pritesh (South Asian Journal of Cancer, 2020)
Background Esophageal cancers, both squamous cell and adenocarcinoma, have poor outcomes with high morbidity and mortality. Our hospital-based registry for the year 2017 to 2018 showed that esophageal cancer constituted 22.7% of annual caseload. Most of our patients present in advanced stages. The aim of this article was to study the role of hormonal receptors in patients with esophageal cancer.Methods This is a single-institution, prospective, observational study in patients with esophageal carcinoma. Hormonal receptors (estrogen receptor [ER]-α and progesterone receptors) were studied in tumor tissue. Of 160 patients, receptor status was analyzed in 133 patients. Chi-square test was used for the correlation of categorical variables. The value of p < 0.05 was considered as statistically significant.Results A total of 133 patients was taken into the study of which 96 were males and 37 were females. The mean age of patients was 52 years. Carcinoma esophagus was predominantly seen in males. Estrogen and progesterone receptors were positive in 9.02 and 4.51% of the study population, respectively. Patients with hormonal receptor positivity presented with poor functional status, higher grades of dysphagia, higher stage, and most of the tumors were poorly differentiated with statistically significant p-values.Conclusion Despite recent advances in various fields of oncology, outcomes of esophageal carcinoma have not improved significantly. Hence, a study of new pathways of pathogenesis in carcinogenesis of esophageal carcinoma is essential. Few recent evidences including our study shows that the hormonal milieu is responsible in the pathogenesis of carcinoma esophagus. The utilization of this data and future study of the role of hormonal therapy might lead to improved outcomes in patients with carcinoma esophagus.
Keywords: carcinoma esophagus; estrogen receptors; progesterone receptors